Evaluation of patient renal function following endovascular aneurysm repair with suprarenal fixation - YingBin Jia; Yun Shi; XiaoDong Guan; Jian Li; BaiMeng Zhang; WeiGuo Fu (Surgical Techniques Development, 2011)
This study aimed to assess the mid-term renal function of abdominal aortic aneurysm patients following suprarenal endovascular repair. From March 2005 to December 2009, 290 abdominal aortic aneurysm patients were included in the study and grouped according to whether they had received infrarenal or suprarenal endovascular aneurysm repair. Suprarenal endovascular aneurysm repair was performed in 173 patients, with a mean age of 72(±8) years (85.0% male). Infrarenal endovascular aneurysm repair was performed in 117 patients, with a mean age of 71(±9) years (90.6% male). Preoperative and one week, 1-, 3-, 6- and 12-month postoperative serum creatinine and cystatin C values were recorded. Estimated glomerular filtration rate was calculated by cystatin-based formula and Cr-based Cockcroft formula. The t-test was used to determine statistical differences between or within groups. All patients received Talent or Zenith endograft. Patients’ characteristics and operative files in the two groups were well matched. Preoperative serum creatinine and cystatin C were 82 (±8) mmol/L and 0.89 (±0.11) mg/L for suprarenal endovascular aneurysm repair, respectively, and 81 (±11) mmol/L and 0.87 (±0.15) mg/L, respectively, for infrarenal endovascular aneurysm repair; no differences were observed between the two groups. Compared to preoperative renal markers within each group, a deterioration in serum creatinine, cystatin C and estimated glomerular filtration rate values was found at one week and 12 months after surgery（P<0.05). A deterioration in cystatin C [SR:(0.93±0.17) mg/L, IR: (0.92±0.31) mg/L] and estimated glomerular filtration rate by cystatin C was also found at six months after surgery（P<0.05). However, no differences in patient serum creatinine, cystatin C and estimated glomerular filtration rate values were observed between groups at each follow-up time interval. There was no greater significant difference in the association of the use of suprarenal fixation with midterm postoperative renal injury than with infrarenal fixation.